Troponins in scuba divers with immersion pulmonary edema. Issue 5 (28th September 2018) - Marlinge, Marion; Deharo, Pierre; Joulia, Fabrice; Coulange, Mathieu; Vairo, Donato; Gaudry, Marine; Egensperger, Mylene; Belkhiri, Laura; Zouggarh, Myriam; Bruzzese, Laurie; Fromonot, Julien; Charnay, Théo; et al.
Abstract : Immersion pulmonary edema (IPE) is a serious complication of water immersion during scuba diving. Myocardial ischemia can occur during IPE that worsens outcome. Because myocardial injury impacts the therapeutic management, we aim to evaluate the profile of cardiac markers (creatine phosphokinase (CPK), brain natriuretic peptide (BNP), highly sensitive troponin T (TnT-hs) and ultrasensitive troponin I (TnI-us) of divers with IPE. Twelve male scuba divers admitted for suspected IPE were included. The collection of blood samples was performed at hospital entrance (T0) and 6 h later (T0 + 6 h). Diagnosis was confirmed by echocardiography or computed-tomography scan. Mean ± S.D. BNP (pg/ml) was 348 ± 324 at T0 and 223 ± 177 at T0 + 6 h ( P <0.01), while mean CPK (international units (IUs)), and mean TnT-hs (pg/ml) increased in the same times 238 ± 200 compared with 545 ± 39, ( P =0.008) and 128 ± 42 compared with 269 ± 210, ( P =0.01), respectively; no significant change was observed concerning TnI-us (pg/ml): 110 ± 34 compared with 330 ± 77, P =0.12. At T0 + 6 h, three patients had high TnI-us, while six patients had high TnT-hs. Mean CPK was correlated with TnT-hs but not with TnI-us. Coronary angiographies were normal. The increase in TnT during IPE may be secondary to the release of troponin from non-cardiac origin. The measurement of TnI in place of TnT permits in some cases to avoid additional examinations, especially unnecessary invasive investigations.